Implications of Gut Microbiota in Neurodegenerative Diseases - Zhang, Haoming; Chen, Yijia; Wang, Zifan; Xie, Gaijie; Liu, Mingming; Yuan, Boyu; Chai, Hongxia; Wang, Wei; Cheng, Ping (Frontiers in Immunology, 2022)
The rapid development of the economy and technology accompanied by improvement in nutrition and healthcare result in the extension of the human lifespan. However, the mobility of neurodegenerative diseases, which include Alzheimer’s disease, Parkinson’s disease, Huntingdon’s disease, and Multiple Sclerosis et al., is increasing. Not only does neurodegenerative harm human living quality mentally and physically, but also adjoint with the heavier and heavier burden to society. Regrettably, due to the complexity of the nervous system and the undetermined etiology and physiopathology, the incurability of neurodegenerative disease haunted numerous researchers from the beginning to the end. That leaves us the enlightened and refreshed impression that the hypothesis that gut microbiota closely involves brain physiology has emerged, which suggested potential therapeutic approaches to neurodegenerative disease. By secreting diverse signaling molecules, gut microbiota bidirectional interacted with the brain through the gut-brain axis, which blood-brain barrier (a functional structure to separate blood from brain tissue and cerebrospinal fluid) served as a ‘customs pass.’ We reviewed current knowledge of possible pathophysiological roles of the microbiota in neurodegenerative diseases. More precisely, we will discuss targeting microbiota composition and microbial metabolites as potential novel therapeutic interventions for these chronic diseases.